Students' Language Attitudes and Politeness as Character Education in the Implementation of Merdeka Belajar Kampus Merdeka (MBKM) - Hariyanti Djafar; Jusmin HJ Wahid; Safrudin Sahmadan (Budapest International Research and Critics University, 2022)
The implementation of character education in higher education has a great impact on the achievement of graduates. In addition to soft skills, it also has an impact on hard skills. Efforts to cultivate student attitudes and politeness are very necessary. This study is carried out to answer why it is necessary to form student attitudes and politeness and how to instill student attitudes and politeness. This study was conducted by using descriptive qualitative method through analyzing the result of observation, interview, and documentation from WhatsApp or SMS from the students. This study presents qualitative data that most of the students whose attitudes and politeness are formed in the Research on Language Teaching and Introduction to Linguistics courses, Giving assignments (project) that are considered as a way to observe students' attitudes and politeness. The results show that students' respect and politeness towards lecturers and assignments can encourage each student's awareness of learning to improve their good character and also their academic field.